2019
DOI: 10.2196/14438
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Polar M430 Activity Monitor in Free-Living Conditions: Validation Study

Abstract: Background Accelerometers, often in conjunction with heart rate sensors, are extensively used to track physical activity (PA) in research. Research-grade instruments are often expensive and have limited battery capacity, limited storage, and high participant burden. Consumer-based activity trackers are equipped with similar technology and designed for long-term wear, and can therefore potentially be used in research. Objective We aimed to assess the cri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 43 publications
(55 reference statements)
2
18
5
Order By: Relevance
“…Correlations for MVPA on previous Polar validation studies varies, but our findings are similarly high compared to findings from Polar M430 [28] and Polar V800 [29]. Similarly, strong correlations for step counting is in accordance with previous studies on Polar V800 [28,29] and Polar M600 [30]. For Oura, we could not find any previous studies on steps, MVPA, or TEE.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Correlations for MVPA on previous Polar validation studies varies, but our findings are similarly high compared to findings from Polar M430 [28] and Polar V800 [29]. Similarly, strong correlations for step counting is in accordance with previous studies on Polar V800 [28,29] and Polar M600 [30]. For Oura, we could not find any previous studies on steps, MVPA, or TEE.…”
Section: Discussionsupporting
confidence: 88%
“…While correlations for EE in the present study are higher than most previous Polar studies [27], it is lower compared to a lab-setting study on Polar Vantage [8] and a free-living study of Polar M430 [28]. Correlations for MVPA on previous Polar validation studies varies, but our findings are similarly high compared to findings from Polar M430 [28] and Polar V800 [29]. Similarly, strong correlations for step counting is in accordance with previous studies on Polar V800 [28,29] and Polar M600 [30].…”
Section: Discussioncontrasting
confidence: 87%
“…In a systematic review of Polar activity trackers [47], we have previously reported that Polar activity trackers show mixed results depending on activity tracker, study setting, and study sample. Furthermore, compared to ndings in a previous Polar M430 validation study [29], with a wider range of weight, height, and age, correlations were lower and MAPEs were higher in the present cohort.…”
Section: Polar M430 Validitycontrasting
confidence: 85%
“…It is waterproof, weighs 51 grams, has up to 20 days of battery life, and cost 150 USD. In a previous study we have shown that the Polar M430 gives valid results for TEE in a wider age-and weight-range, when compared to a hip-worn ActiGraph wGT3X-BT accelerometer (ActiGraph, Pensacola, FL, USA) [29].…”
Section: Instrumentsmentioning
confidence: 98%
“…This indicate that the AT was mostly well tolerated and provided valuable data regarding participants' PA intensity levels and daily activity (77). In a previous study, we have also shown that Polar M430 is valid to measure total energy expenditure (78).…”
Section: Measurement Of Physical Activitymentioning
confidence: 70%